Fiberoptic bronchoscopy in the diagnosis and therapeutic decision for respiratory infections in hematological febrile neutropenic patients - Bento, Luiza; Paz, Alessandra; Rigone, Lisandra; Fischer, Gustavo; Bittencourt, Rosane; Silla, Lucia; Daudt, Liane (Clinical and Biomedical Research, 2014)
Background: Febrile neutropenia is a common complication in patients undergoing chemotherapy or hematopoietic Stem Cell Transplantation (HSCT). Flexible fiberoptic bronchoscopy has been used to aid in the diagnosis of pulmonary diseases. However, there is no consensus regarding the benefit of the exam in establishing diagnosis and in changing the treatment of lung disease in this context. Previous retrospective studies, quite heterogeneous and with non-HIV immunocompromised patients, showed that the yield of fiberoptic bronchoscopy in establishing etiology ranges from 13% to 81%, and in changing therapy, from 5% to 51%. Aim: To evaluate the efficiency of Fiberoptic bronchoscopy and the procedure-related risk for neutropenic patients with hematologic malignancy. Methods: This retrospective cross-sectional study analyzed the medical records of patients with hematologic malignancy with febrile neutropenia who had undergone diagnostic fiberoptic bronchoscopy between January 2011 and December 2012 at the Hospital de Clínicas de Porto Alegre. Results: A total of 45 patients were included: 18 (36%) tested positive for bronchoalveolar lavage, with change in therapeutic management occurring for 95% of them. The procedure-related risk was 2.2%, with one patient showing desaturation immediately after the procedure. Conclusion: Despite the limited number of patients, our findings indicate that fiberoptic bronchoscopy in neutropenic patients is safe, and the results are similar to those previously reported.